2017
DOI: 10.1177/0003702817711700
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of Rhodamine B in Condiments Using Surface-Enhanced Resonance Raman Scattering (SERRS) Silver Nanowires as Substrate

Abstract: In this paper, a facile large-scale preparation of surface-enhanced resonance Raman scattering (SERRS) substrates for the determination of Rhodamine B (RhB) based on silver nanowires (Ag NWs) has been developed. The morphology, structure, and properties of as-prepared Ag NWs are characterized using ultraviolet-visible (UV-Vis) spectroscopy, field emission scanning electron microscopy (FE-SEM), and X-ray diffraction (XRD), respectively. Ag NWs were assembled onto glass slides through a self-assembly method. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
1
4
0
1
Order By: Relevance
“…Spectra were observed with films made from the neat LiF/HCl material, but not from a 1:4-diluted LiF/HCl solution or from the HCl solution. For the neat LiF/HCl films, the SERS response for Rhodamine B was linear with concentration and consistent with prior literature reports [4] obtained with a different substrate. Intrinsic fluorescence of the Rhodamine B was greatly reduced for these samples compared to dried drops of neat Rhodamine B solution.…”
Section: Resultssupporting
confidence: 90%
“…Spectra were observed with films made from the neat LiF/HCl material, but not from a 1:4-diluted LiF/HCl solution or from the HCl solution. For the neat LiF/HCl films, the SERS response for Rhodamine B was linear with concentration and consistent with prior literature reports [4] obtained with a different substrate. Intrinsic fluorescence of the Rhodamine B was greatly reduced for these samples compared to dried drops of neat Rhodamine B solution.…”
Section: Resultssupporting
confidence: 90%
“…Molecular docking studies have confirmed damaging interaction of RhB with DNA in humans . In light of these observations, research efforts are being dedicated for early detection and analysis of trace concentrations of RhB in food safety and pharmacokinetics, in terms of qualitative and quantitative determination. Different techniques such as capillary electrophoresis, UV–visible spectrophotometry, spectrofluorometry, enzyme-linked immunosorbent assay, high-performance liquid chromatography, chemiluminescence, and the plasmon-coupled emission platform to name a few have been developed for sensing RhB at very low concentrations. While the surface enhanced resonance Raman scattering (SERRS) platform supported by Ag nanowires as a plasmonic substrate could lower the detection limit to nanomolar levels, our earlier work using the SPCE platform lowered the detection limit to 0.1 picomolar concentrations using AgCD (silver decorated carbon dots) as efficient nanoantennas in the SPCE platform .…”
Section: Results and Discussionmentioning
confidence: 99%
“…58−67 Different techniques such as capillary electrophoresis, UV−visible spectrophotometry, spectrofluorometry, enzyme-linked immunosorbent assay, highperformance liquid chromatography, chemiluminescence, and the plasmon-coupled emission platform to name a few have been developed for sensing RhB at very low concentrations. While the surface enhanced resonance Raman scattering (SERRS) platform supported by Ag nanowires as a plasmonic substrate could lower the detection limit to nanomolar levels, 65 our earlier work using the SPCE platform lowered the detection limit to 0.1 picomolar concentrations using AgCD (silver decorated carbon dots) as efficient nanoantennas in the SPCE platform. 18 Nevertheless, there are no reports that discuss further lowering this detection limit.…”
Section: Soluplus Mediated Aunps: Spce Nanointerfacesmentioning
confidence: 96%
“…5c and d. This might be related to the shi in the peaks due to the enhanced resonance Raman scattering 41,42 effect for 514 nm laser excitation as RhB has a sharp peak at 552 nm in UV-vis absorption, 43,44 which is close to the 514 nm excitation laser. It can be seen from Fig.…”
Section: Sers Experiments On Rhodamine Bmentioning
confidence: 92%